Away from chaos : the Middle East and the challenge to the West - Kepel, Gilles (Columbia University Press, 2020)
"Away from Chaos is a sweeping political history of the global ramifications of Middle East politics. Starting with Arab nationalism in the postwar era and tracing the international ripple effects of local conflicts in the region up to the present, Kepel has written a clever and easily digestible narrative of long-term chaotic events throughout the Middle East while seamlessly incorporating on-the-ground observations and personal experiences from the politicians and civilians who lived through them. From the Yom Kippur/Ramadan war of 1973 to the aftermath of the various Arab Springs of 2011 to the return of Russian power in the Levant, Away from Chaos seeks to make sense of and weave together the various political threads that run through Middle East politics and ties them to their implications on the larger global stage. With his signature persuasive and lively style, Kepel uses his forty years of experience in the region to create a straightforward chronology of events that traces the causes of tension in the Middle East and the fault lines to emerge as a result of our current actions"--